Avtor, junak in sporočilnost v zgodnji kratki prozi Vladimirja Bartola - Virk, Tomo (Slavistična revija, 2014)
This article deals with the relationship between the author and his manifestations using the example of Vladimir Bartol's early short prose. It shows that the messages of Bartol's texts ought not to be understood with reference to the author's views, even if the views are applied to the narrator or other literary personages.
Keywords: author; avtor; Bartol, Vladimir, 1903-1967; kratka proza; literarni junak; literary protagonist; narrator; pripovedovalec; short prose; Slovene literature; slovenska književnost; svetovni nazor; world view